Akt Signaling and Nitric Oxide Synthase as Possible Mediators of the Protective Effect of N-acetyl-L-cysteine in Prediabetes Induced by Sucrose - Castro, María Cecilia (2024)
The aim of this work was to evaluate possible mechanisms involved in the protective effect of N-acetyl-L-cysteine (NAC) on hepatic endocrine-metabolic, oxidative stress, and inflammatory changes in prediabetic rats. For that, normal male Wistar rats (60 days old) were fed for 21 days with 10% sucrose in their drinking water and 5 days of NAC administration (50 mg/kg, i.p.) and thereafter, we determined: serum glucose, insulin, transaminases, uric acid, and triglyceride levels; hepatic fructokinase and glucokinase activities, glycogen content, lipogenic gene expression; enzymatic and non-enzymatic oxidative stress, insulin signaling pathway, and inflammatory markers. Results showed that alterations evinced in sucrose-fed rats (hypertriglyceridemia, hyperinsulinemia, and high liver fructokinase activity together with increased liver lipogenic gene expression and oxidative stress and inflammatory markers) were prevented by NAC administration. P-endothelial nitric oxide synthase (P-eNOS)/eNOS and pAKT/AKT ratios, decreased by sucrose ingestion, were restored after NAC treatment. In conclusion, the results suggest that NAC administration improves glucose homeostasis, oxidative stress, and inflammation in prediabetic rats probably mediated by modulation of the AKT/NOS pathway. Administration of NAC may be an effective complementary strategy to alleviate or prevent oxidative stress and inflammatory responses observed in type 2 diabetes at early stages of its development (prediabetes).